Teaching Ability of Students Field Experience Practices in Palembang - Aradea, Riswan; Hamzah, Syukri (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The purpose of this study is to describe teaching ability of field experience practice students at SMA/SMK in Palembang. The method used is descriptive method. Research population consists of students and tutors where students carry out practice as much five schools, Sample subject study taken as many as 20% of which amounted to 31 high school students, 46 vocational students, while the sample of civil servant teachers in this study amounted to 8 senior high school civil servants and 3 vocational high school civil servants. Data collection techniques using questionnaire for good students and tutors. Analysis data by percentage. The conclusion of the study shows that the overall teaching ability of field experience practice students at SMA/SMK in Palembang City is quite good. This paper indicates that the teaching skills of field experience practice students need to be further improved so that the application of basic teaching skills can be carried out as well as possible.